Effects of socioeconomic factors on prognosis of breast cancer in patients younger than forty years - ALKIŞ, HİLAL (My University, 2021)
Purpose or Objective To investigate effects of socioeconomic factors on prognosis of breast cancer among women with breast cancer younger than forty (<40) years of age. Materials and Methods A total of 873 breast cancer patients attended between October 2006 and November 2015 were included in the study. Number of patients <40 years was 265 (30.4%). Socioeconomic properties were recorded as education status (nonliterate, primary school, secondary school, high school, and university), household income (<600, 600-1600, >1600 Turkish Liras) and living in urban or rural areas. Clinicopathologic features (hormone receptor status, tumor stage, tumor grade) and survival of the patients were recorded. Results Median age of all patients was 47 (20-85). Estrogen Receptor (ER) and Progesterone Receptor (PR) were positive in 57% (n=151) and 63% (n=167) of patients <40 years, respectively, and, ER and PR positivity were 72.2% (439) and 70.7% (430) in patients over 40 years, respectively (p<0.001). Advanced disease at diagnosis, larger tumors and ER negativity were more common in patients <40 years who were nonliterate, had lower income and worse socioeconomic status (p<0.001). Five year and ten year survival rates related to these factors at this group of age were 86% and 74%, respectively and were 90% and 85% in patients over 40 years, respectively. Conclusion Socioeconomic factors affect the tumor biology and clinical progress of breast cancer patients in all groups of age. Furthermore, prognosis of patients with breast cancer <40 years may be worsened by lower socioeconomic status.